Plant Responses to Biotic Stress: Old Memories Matter - Anirban Bhar; Amrita Chakraborty; Amit Roy (Plants, 2021)
Plants are fascinating organisms present in most ecosystems and a model system for studying different facets of ecological interactions on Earth. In the environment, plants constantly encounter a multitude of abiotic and biotic stresses. The zero-avoidance phenomena make them more resilient to such environmental odds. Plants combat biotic stress or pathogenic ingression through a complex orchestration of intracellular signalling cascades. The plant–microbe interaction primarily relies on acquired immune response due to the absence of any specialised immunogenic cells for adaptive immune response. The generation of immune memory is mainly carried out by T cells as part of the humoral immune response in animals. Recently, prodigious advancements in our understanding of epigenetic regulations in plants invoke the “plant memory” theory afresh. Current innovations in cutting-edge genomic tools have revealed stress-associated genomic alterations and strengthened the idea of transgenerational memory in plants. In plants, stress signalling events are transferred as genomic imprints in successive generations, even without any stress. Such immunogenic priming of plants against biotic stresses is crucial for their eco-evolutionary success. However, there is limited literature capturing the current knowledge of the transgenerational memory of plants boosting biotic stress responses. In this context, the present review focuses on the general concept of memory in plants, recent advancements in this field and comprehensive implications in biotic stress tolerance with future perspectives.